Maintaining the integrity of the South African university: The impact of ChatGPT on plagiarism and scholarly writing - Singh, M. (South African Journal of Higher Education, 2023)
Recent advancements in artificial intelligence (AI) have reignited discussions about the value of the university and its role in producing and facilitating knowledge. The invention of ChatGPT has led to differing responses in the academy, with some welcoming its abilities and others fearing that it may undermine what schools and universities do, calling it “apocalyptic” (Green 2022). These aspects impact the integrity of the academy and are therefore a fundamental contribution to the debate. The impact, as well as the perceived impact, of AI on teaching and learning in higher education has been consistently documented in popular media. Therefore, the aim of this article is to understand the impact of ChatGPT on plagiarism and scholarly writing. It contributes to the under-researched academic discourse of generative artificial intelligence and teaching and learning by garnering the views of three established professors in South Africa. The findings from this qualitative endeavour demonstrate that, for these professors, these kinds of technology are welcome, and students need to be taught how to engage with them rather than vilifying them. Much of the responsibility rests on the lecturers and the university to create a teaching and learning environment that allows for these technologies to enter the classroom, especially in the way we assess.